Implementation of Scientific Approach with Concrete Materials to Improve Mathematics Learning Outcames about Plane Figures to Fourth Grade Students of SDN Mengkowo In Academic Year of 2019/2020 - Sumayyah Sumayyah; Wahyudi Wahyudi; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The purposes of the study were: (1) to describe the steps of scientific approach with concrete materials in improving mathematics learning outcomes about plane figures, (2) to improve mathematics learning outcomes about plane figures with scientific approaches and concrete materials, (3) to describe obstacles and solutions for implementing scientific approaches with concrete media in improving mathematics learning outcomes about plane figures. The study was classroom action research conducted in three cycles and six meetings. The subjects were teacher and 31 students of fourth grade at SDN Mengkowo. Types of data were qualitative data and quantitative data. Data collection techniques used observation, interviews, and tests. Data validity used triangulation of techniques and triangulation of sources. Quantitative and qualitative data analysis included data reduction, data presentation, and drawing conclusions. The results indicated that: (1) the steps of scientific approach with concrete materials involved: (a) observing concrete materials, (b) asking questions based on materials, (c) gathering information from the media, (d) experimenting, and (e) communicating; (2) the implementation of scientific approach with concrete materials improved mathematics learning outcomes about plane figures to fourth grade students of SDN Mengkowo in academic year of 2019/2020; (3) the obstacle was some students found difficulties to understand the worksheet while the solution was the teacher asked students to pay attention to the teacher after receiving the worksheet.